2023
DOI: 10.3390/foods12020252
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Probiotics by Oil-in-Water Emulsification Technique Improves Cell Viability under Different Storage Conditions

Abstract: Probiotics are associated with health benefits to the host. However, their application can be limited due to a decrease in cell viability during processing, storage, and passage through the gastrointestinal tract. Microencapsulation is a simple and efficient alternative to improve the physical protection and stability of probiotics. The present study aimed to produce and characterize alginate or gelatin-based microparticles containing Lactobacillus acidophilus NRRL B-4495 or Lactiplantibacillus plantarum NRRL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The EE using the emulsion technique is like other reports but uses different encapsulating agents. Elvan et al [35] found EE above 90%, when using whey protein concentrate and xylan, while da Silva et al [36] obtained lower efficiencies (81.1 and 89.61%) using porcine gelatin as the encapsulating matrix. Studies using sodium alginate as an encapsulating agent show variable results, Gul and Dervisoglu [37] report efficiencies of 86.71% and 95.25%, while in another study [36] they obtained <1.0%.…”
Section: Encapsulation Efficiencymentioning
confidence: 98%
See 1 more Smart Citation
“…The EE using the emulsion technique is like other reports but uses different encapsulating agents. Elvan et al [35] found EE above 90%, when using whey protein concentrate and xylan, while da Silva et al [36] obtained lower efficiencies (81.1 and 89.61%) using porcine gelatin as the encapsulating matrix. Studies using sodium alginate as an encapsulating agent show variable results, Gul and Dervisoglu [37] report efficiencies of 86.71% and 95.25%, while in another study [36] they obtained <1.0%.…”
Section: Encapsulation Efficiencymentioning
confidence: 98%
“…Elvan et al [35] found EE above 90%, when using whey protein concentrate and xylan, while da Silva et al [36] obtained lower efficiencies (81.1 and 89.61%) using porcine gelatin as the encapsulating matrix. Studies using sodium alginate as an encapsulating agent show variable results, Gul and Dervisoglu [37] report efficiencies of 86.71% and 95.25%, while in another study [36] they obtained <1.0%. The high efficiency reported in our study may be due to the use of alginate in combination with a prebiotic (lactulose), as mentioned for the extrusion technique, since it could act as a co-encapsulating agent, improving barrier properties.…”
Section: Encapsulation Efficiencymentioning
confidence: 98%
“…The World Health Organization states that a successful probiotic product must contain an adequate amount of viable microorganisms. A colonies per gram (CFU) or milliliter (mL) of 10 6 -10 7 is essential for conferring health benefits [8]. Drying probiotic cultures for industrial purposes reduces transportation costs and storage requirements [9].…”
Section: Introductionmentioning
confidence: 99%